DAMPAK PEMASARAN RAMAH LINGKUNGAN TERHADAP MANAJEMEN RANTAI PASOKAN DI PASAR INDUSTRI - Mona Karina (GoAcademica Research dan Publishing, 2020)
Green marketing and supply chains have attracted the attention of academics and practitioners in the past decade. However, no holistic framework has yet been developed on how to build environmentally friendly industrial and corporate brands. Whether an environmentally friendly/sustainable supply chain can be integrated with marketing an environmentally friendly industry in building a more environmentally friendly organization and industrial brand remains unclear. In addition, little is known about factors in developing new environmentally friendly industrial products or how new environmentally friendly industrial products are adopted by organizations or companies. In addition, we know very little about whether and how environmentally friendly supply chains enable the development of new environmentally friendly industrial products. This particular issue aims to reflect the latest advancements in marketing green industries, sustainable/green supply chains and their interactions in green industry brands, and to explore future research directions.